Can compressive thoracic cord lesions cause a pure lower motor neurone syndrome?. Issue 1 (3rd October 2018) - Kok, Chin Yong; Chandrashekar, Hoskote; Turner, Christopher; Manji, Hadi; Rossor, Alexander M
Abstract : Compressive lesions of the spinal cord usually cause a syndrome of upper motor neurone weakness, spasticity and sensory loss below the level of the lesion. It has long been recognised that compressive cervical cord lesions may present as isolated lower motor neurone weakness of the upper limbs, a syndrome termed cervical spondylotic amyotrophy. We describe two patients presenting with isolated lower motor neurone weakness of the lower limbs in association with a compressive cord lesion at T11/12, a condition we have termed thoracic spondylotic amyotrophy.